Resolving Size Distribution of Black Carbon Internally Mixed With Snow: Impact on Snow Optical Properties and Albedo. Issue 6 (25th March 2018) - He, Cenlin; Liou, Kuo‐Nan; Takano, Yoshi
Abstract: We develop a stochastic aerosol‐snow albedo model that explicitly resolves size distribution of aerosols internally mixed with various snow grains. We use the model to quantify black carbon (BC) size effects on snow albedo and optical properties for BC‐snow internal mixing. Results show that BC‐induced snow single‐scattering coalbedo enhancement and albedo reduction decrease by a factor of 2–3 with increasing BC effective radii from 0.05 to 0.25 μm, while polydisperse BC results in up to 40% smaller visible single‐scattering coalbedo enhancement and albedo reduction compared to monodisperse BC with equivalent effective radii. We further develop parameterizations for BC size effects for application to climate models. Compared with a realistic polydisperse assumption and observed shifts to larger BC sizes in snow, respectively, assuming monodisperse BC and typical atmospheric BC effective radii could lead to overestimates of ~24% and ~40% in BC‐snow albedo forcing averaged over different BC and snow conditions. Plain Language Summary: Snow albedo is a key element in the Earth and climate system, which is regulated by snow and impurity properties. Snow albedo can be substantially reduced by the presence of light‐absorbing aerosols, such as black carbon (BC). However, very little attention has been paid to the impact of BC size on snow albedo reduction, while observations have shown large variations in BC size distribution in the atmosphere and snow. In this study, we have developed a new aerosol‐snow albedo model to resolve aerosol size distribution mixed within various snow grains. We find that the BC effects on snow albedo decrease with increasing BC effective sizes and are also influenced by different assumptions of BC size distributions. We further develop parameterizations for BC size effects for application to climate models. This study points toward an urgent need for not only better model characterizations but also extensive measurements of BC size distribution in snow. Key Points: A new stochastic aerosol‐snow albedo model is developed to resolve aerosol size distribution internally mixed in various snow grains BC‐induced snow single‐scattering coalbedo enhancement and albedo reduction significantly decrease with increasing BC effective radii Polydisperse BC leads to smaller single‐scattering coalbedo enhancement and albedo reduction than monodisperse BC with same effective radii